High-Temperature Deformation Constitutive Model of Zircaloy-4 Based on the Support Vector Regression Algorithm during Hot Rolling - Cao, Yuan; Cao, Jianguo; Wang, Leilei; Song, Chunning; Li, Fang; Zhang, Pengfei (Journal of materials engineering and performance, 2022)
Due to the small range of plastic deformation temperatures during hot rolling of Zircaloy-4 plates, it is important to determine the appropriate flow behaviors for plate profile control of Zircaloy-4 plates. The developed microstructures and mechanical properties of Zircaloy-4 are evaluated by metallographic observations and Gleeble-3800 thermal simulation tester. To meet the need of data with small-sample properties, the support vector regression (SVR) algorithm is adopted to predict the constitutive model of Zircaloy-4, and the improved particle swarm optimization algorithm (IPSO) is used to optimize parameters of SVR algorithm. Meanwhile, results indicate that the correlation coefficient ( R 2 ) value of zirconium alloy constitutive model is 96.805%. Based on employed algorithm, comparing with modified Arrhenius model, the results show the superiority of IPSO-SVR algorithm. This provides an important theoretical basis for FE simulation of controlling the Zircaloy-4 plate shape during hot rolling process.